Digital Transformation of Human Resource Management in Facing the Impact of AI And Automation on Its Role - Munthe, Richa Afriana; Ucok, Imran Al (Jurnal Ilmu Sosial Mamangan, 2025)
Progress rapid artificial intelligence (AI) and automation has transform Management Source Power Human (HR), shifting HR's role of function administrative become partners strategic business. Research This aim for analyze digital transformation of HR in respond the impact of AI and automation, with focus on the Indonesian context. Through approach qualitative studies case collective, data collected through interview in- depth discussion group focused, and observation in eight organization big cross industry. Findings show existence evolution significant in role of HR, the emergence of position new digital- based, as well as need competence hybrid between digital skills and soft skills in HR professionals. Challenges main identified covering gap digital competence, resistance to changes, limitations infrastructure, and complexity integration system. Successful organizations do digital transformation implements development capability in a way structured learning program sustainable, collaborative cross function, as well as adoption technology in a way gradual. Research This give contribution in the form of development framework conceptual integrated HR digital transformation in emerging markets and recommendations practical for organization in face the complexity of AI and automation in HR functions.